2011
DOI: 10.5141/jefb.2011.036
|View full text |Cite
|
Sign up to set email alerts
|

Ecological responses of natural and planted forests to thinning in southeastern Korea: a chronosequence study

Abstract: Effects of forest thinning on community level properties have not been understood yet in Korea. We investigated regeneration patterns and trajectories after a disturbance by applying a chronosequence approach. Light availability, litter and woody debris cover, and species composition were determined for twenty 50 m line-transect samples representing a disturbance duration gradient (within 11 years). Environmental factors such as light availability and coverage of woody debris and litter changed abruptly after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Cho et al (2011) analyzed the influences of thinning on understory vegetation and abiotic variables in natural and planted broadleaved forests using a chronosequence approach. Son et al (2004) found some management implications from relatively short-term observations in Larix leptolepis plantations.…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al (2011) analyzed the influences of thinning on understory vegetation and abiotic variables in natural and planted broadleaved forests using a chronosequence approach. Son et al (2004) found some management implications from relatively short-term observations in Larix leptolepis plantations.…”
Section: Introductionmentioning
confidence: 99%